Imposition of Sanctions Criminal Personnel for Torture in the Investigation Process - Sonya Isabella Manik (Universitas Negeri Semarang, 2021)
The aim of this research is to find out how the legal process for police officers who abuse suspects and how the process of arresting and examining suspects. The research used the normative juridical research method, and it is found that law enforcement against POLRI members requires a legal basis that is used as a formal juridical basis in committing a crime. The legal basis in question is the Criminal Procedure Code, namely Law No. 8 of 1981. In connection with the subject that is a suspect or defendant is a member of the National Police, besides the Criminal Procedure Code, there are several other regulations that are used as a juridical basis in implementing legal proceedings against members of the Indonesian National Police who commit criminal acts as a legal basis are stipulated at some laws, such as Law Number 2 of 2002 concerning the Indonesian National Police, Law Number 14 of 2011 concerning the Professional Code of Ethics for the State Police of the Republic of Indonesia,Â and Government Regulation Number 3 of 2003 concerning the Implementation of General Judicial Institutional Techniques for Members of the Indonesian National Police. This research also highlighted that the task of arresting officers is carried out by the state police of the Republic of Indonesia by showing a letter of assignment and giving the suspect an arrest warrant stating the suspect's identity (full name, age, occupation, religion, and address/residence) and state the reasons for the arrest and a brief description of the criminal case suspected and the place where he was examined. In the event of being caught in the red, the arrest is carried out without a warrant, provided that the arrest must immediately hand over the person caught and the evidence available to the investigator or the closest assistant investigator.